(untitled) (Medical Forum Monthly, 2024)
Objective: Isoniazid Hydrochloride is a drug used for prophylaxis and treatment of tuberclusis with the combination of other drugs. Study Design: Experimental study. Place and Duration of Study: This study was conducted at the at Shahida Islam Medical College, Lodhran, during July 2017 to December 2017. Materials and Methods: The present study was conducted on 30 rabbits which were group from A to C consisting of 10 rabbits in each group with the weight of 2500-3500 grams. The first control group A was fed on fresh alfa alfa and water, the second group B was given 50 mg per kilogram body-weight of INH dissolved in water twice a day and the third group C was given INH with curcuma longa 100 mg twice a day dissolved in water in powder form. The blood samples were taken on day 01, 10 and 20. Results: The AST level has non-significant changes in group A where P value was 0.21. The changes in group B and C are significant where P value in both were 0.01. In group B the AST level raised high during initial ten days where as AST level came down on day 20 probably due to addition of curcuma longa. The level of AST has remained close to normal in group C due to addition of high dose of curcuma longa. The liver paranchymal damage was observed on treatment with INH in group B. The restoration of hepatocytes architecture and minimum fibrosis was observed in group C. Conclusion: Curcuma longa has protective effect against all the toxic agents of the liver. Curcumin has several group which function as antioxidant20. It has been proved practically that curcuma longa is very effective against the Hepatotoxic agents.